2017
DOI: 10.1166/asl.2017.10803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing Concentrations of Tween 80 and Sorbitol as Surfactants and Cosurfactans Against the Physical Stability Properties of Palm Oil Microemulsion

Abstract: Palm oil is one of the fatty oil can used as the oil phase in the microemulsion system. The purpose of this research was to identify the effect of increasing concentration of combination of surfactant and cosurfactant on the physical stability of palm oil microemulsion. This oil was formulated into microemulsion system by increasing concentration of combination of tween 80 and sorbitol (1:1) in various concentrations, which were 54%, 56%, 58% and 60% as surfactant and cosurfactant component. The evaluation inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Values of viscosity of 22.4-26.69 cP were reported in rheological study of O/W microemulsions with minoxidil, being associated with the composition based on a total amount of S/CoS mixture of 53% [83]. As the concentration of S/CoS blend increases between 54-60%, viscosity can attain 637.47-808.20 cP, as it was observed in the evaluation process of O/W microemulsions with palm oil 6%, without changing the model of viscosity [95]. In-depth studies were conducted to assess rheological properties of O/W microemulsions using a mixture of Tween 80/PG (2:1) (10-30%) as a powerful solubilizer for cinnamon essential oil 2-5%.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Values of viscosity of 22.4-26.69 cP were reported in rheological study of O/W microemulsions with minoxidil, being associated with the composition based on a total amount of S/CoS mixture of 53% [83]. As the concentration of S/CoS blend increases between 54-60%, viscosity can attain 637.47-808.20 cP, as it was observed in the evaluation process of O/W microemulsions with palm oil 6%, without changing the model of viscosity [95]. In-depth studies were conducted to assess rheological properties of O/W microemulsions using a mixture of Tween 80/PG (2:1) (10-30%) as a powerful solubilizer for cinnamon essential oil 2-5%.…”
Section: Discussionmentioning
confidence: 78%
“…In pendant drop model, γ L/G varied between 32.57-37.36 mN/m, describing stability of the systems characterized by low superficial tensions, and consequently low interfacial tensions between oil and water phases. In the study of Yati K. et al, the values of γ L/G reported after applying De Nouy ring method for microemulsions stabilized with Tween 80 and sorbitol, were placed between 39.76-43.4 mN/m [95]. Likewise, in CA model γ L/G was evaluated as a parameter implied in drop dynamics, succeeding adhesion promotion.…”
Section: Discussionmentioning
confidence: 99%